Comparison of Carbapenem Resistance Detected by the BD Phoenix Automated System in Enterobacteriaceae Isolates with E-Test Method. Issue 3 (2022) - Celik, Mehmet; Sunnetcioglu, Mahmut; Guducuoglu, Huseyin; Arslan, Yusuf; Akyuz, Sumeyye; Baran, Ali Irfan
No abstract available